2021
DOI: 10.3390/rs13071396
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat Island Formation in Greater Cairo: Spatio-Temporal Analysis of Daytime and Nighttime Land Surface Temperatures along the Urban–Rural Gradient

Abstract: An urban heat island (UHI) is a significant anthropogenic modification of urban land surfaces, and its geospatial pattern can increase the intensity of the heatwave effects. The complex mechanisms and interactivity of the land surface temperature in urban areas are still being examined. The urban–rural gradient analysis serves as a unique natural opportunity to identify and mitigate ecological worsening. Using Landsat Thematic Mapper (TM), Operational Land Imager/Thermal Infrared Sensor (OLI/TIRS) and Moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…Note that a 25 km buffer size in this analysis was centered around a point feature (circle in Figure 1f) while the buffer area from the other analyses was an extension of urban raster cells with a size of 10 km (i.e., selecting raster cells within 10 km of MODIS urban grid cells; black/orange cells in Figure 1). The choices of these buffer sizes are adapted from UHI studies (Athukorala & Murayama, 2021; Rasul et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Note that a 25 km buffer size in this analysis was centered around a point feature (circle in Figure 1f) while the buffer area from the other analyses was an extension of urban raster cells with a size of 10 km (i.e., selecting raster cells within 10 km of MODIS urban grid cells; black/orange cells in Figure 1). The choices of these buffer sizes are adapted from UHI studies (Athukorala & Murayama, 2021; Rasul et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Land surface temperatures can be affected by error ratios because of the calibration noises in Landsat 8 Band 11 and the reliance on Band 11 measurements [16,51,52]. Hence, the average of the two bands' mean brightness temperatures was used as the average temperature.…”
Section: Macro-scale Uhi Investigationmentioning
confidence: 99%
“…These changes have been related to land use/ land cover, where the urban growth in the high density population areas as Greater Cairo showed the greatest increase in thermal radiation from land surfaces (Abutaleb et al, 2015). Recent studies (Athukorala and Murayama 2021) have shown differences in LST along an Urban-rural gradient, between the day and night, and the spatial characteristics of nighttime surface urban heat island effects over Greater Cairo. However, the long-term changes of LST have not been studied, and relatively little attention has been given to specific urban land covers that exacerbate heating or provide cooling.…”
Section: Introductionmentioning
confidence: 99%